Relapsing peritonitis caused by Corynebacterium amycolatum in a patient undergoing continuous ambulatory peritoneal dialysis: A case report - Sonmezer, Meliha Cagla; Ertem, Günay Tuncer; Yetkin, Meltem Arzu; Yıldız, Eda; Oral, Behiç (International Journal of Infection Control, 2013)
Peritonitis is a common clinical problem in patients treated by peritoneal dialysis. Corynebacterium species are an uncommon cause of continuous ambulatory peritoneal dialysis ( CAPD) related to peritonitis and Corynebacterium amycolatum (C. amycolatum) is rarely described in the literature. In the present case, we report relapsing peritonitis caused by C. amycolatum in a patient undergoing CAPD in a 55-year-old Turkish woman with normal immune function. Pathological diagnosis was nephrotic syndrome. The patient was treated with intraperitoneal (IP) vancomycin treatment. No bacterial growth was detected in conventional culture media, however, bacteria was isolated from the peritoneal fluid culture on second day by BACTEC (Becton Dickinson, USA) automated blood culture system. The strain was identified as C. amycolatum according to the results of Gram stain, colony morphology and numerous biochemical tests including API CORYNE kit (bioMerieux, France). To our knowledge, this is the first report of relapsing peritonitis caused by C. amycolatum in a patient undergoing CAPD. In conclusion, this bacterium should be kept in mind as a possible agent in CAPD patients with peritonitis and peritoneal fluid samples should be inoculated into automated culture systems.